Insights into a First Millennium BC (800 – 400 cal BC) Social Network: Excavations at Las Orquídeas in the Northern Ecuadorian Sierra - Dyrdahl, Eric; Montalvo, Carlos (Journal of Global Archaeology, 2022)
Interregional interaction long has been a central theme in Ecuadorian archaeology. However, outside of a few studies from late prehispanic contexts, little evidence of craft production has been identified, with limited examples that relate to long-distance exchange. Excavations at Las Orquídeas, a Late Formative (800 – 400 cal BC) site located on the outskirts of the modern city of Ibarra, have recovered the most diverse array of crafting activities in prehispanic Ecuador. We present the first detailed examination of 278 m2 of excavations, documented contexts, and some important artifact classes (ceramics, obsidian, malacological remains) since our doctoral dissertations. We argue that the first millennium BC inhabitants of Las Orquídeas participated in a long-distance network that involved important social events in which exotic jewelry was exchanged. The population at Las Orquídeas obtained unworked non-local raw materials to craft distinctive jewelry and participate in the network.